A 23-Year Observational Follow-Up Clinical Evaluation of Direct Posterior Composite Restorations - Marie O. von Gehren; Stefan Rüttermann; Georgios E. Romanos; Eva Herrmann; Susanne Gerhardt-Szép (MDPI AG, 2023)
The purpose of this observational follow-up clinical study was to observe the quality of posterior composite restorations more than 23 years after application. A total of 22 patients, 13 male and 9 female (mean age 66.1 years, range 50-84), with a total of 42 restorations attended the first and second follow-up examinations. The restorations were examined by one operator using modified FDI criteria. Statistical analysis was performed with the Wilcoxon Mann-Whitney U test and Wilcoxon exact matched-pairs test with a significance level of p = 0.05. Bonferroni-Holm with an adjusted significance level of alpha = 0.05 was applied. With the exception of approximal anatomical form, significantly worse scores were seen for six out of seven criteria at the second follow-up evaluation. There was no significant difference in the first and second follow-up evaluations in the grades of the restorations with regard to having been placed in the maxilla or mandible, as well as for one-surface or multiple-surface restorations. The approximal anatomical form showed significantly worse grades at the second follow-up when having been placed in molars. In conclusion, the study results show that significant differences regarding FDI criteria in posterior composite restorations occur after more than 23 years of service. Further studies with extended follow-up time and at regular and short time intervals are recommended.